Special Issue of the Asian Journal of Business Ethics on Global Survey of Business Ethics (GSBE) Reports 2022–2024 from Asia, Australia, and Russia: Philippines - Teehankee, Benito L. (Archīum Ateneo, 2024)
The Philippines, a Southeast Asian archipelago, has a rich cultural history shaped by influences from Hindu empires, Spanish colonization, American governance, and brief Japanese occupation. The country operates under a democratic system based on the 1987 Constitution, with Filipino and English as its official languages. Despite economic growth since 1999, challenges such as poverty, corruption, and natural disasters persist. The business sector, historically focused on profit, has shown a gradual shift towards social responsibility, as reflected in evolving corporate governance practices and ethical entrepreneurship. A significant body of literature now emphasizes the role of business in poverty alleviation, corporate governance, Catholic social thought, environmental sustainability, and humanistic management. Recent studies also highlight the influence of virtue ethics and Catholic teachings on corporate practices. The teaching of business ethics in the Philippines has increasingly focused on social responsibility, good governance, and aligning business practices with sustainability goals. Moving forward, major ethical issues for businesses include artificial intelligence, environmental sustainability, economic inequality, and the need for ethical leadership. Business ethics research and pedagogy have made significant strides, though further integration of local cultural perspectives and more effective education on persistent challenges is essential.